1990
DOI: 10.1007/bf00194228
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of three patients with the ?ring syndrome?, including familial transmission of ring 5, and estimation of reproductive risks

Abstract: We report three cases of ring chromosome 5 [r(5)], two familial (mother and daughter) and one sporadic. The phenotype resembled that of the "ring syndrome" with prenatal onset of short stature, growth retardation, mild facial dysmorphism and normal psychomotor development. Extended metaphase and prometaphase chromosome preparations using G-, R- and Q-banding and scanning electron microscopy (SEM) failed to demonstrate deletion in the ring 5. Flow karyotype using the FACS cell sorter and peak area analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Seizures are not a feature of the well-known "cri du chat" (5p deletion) syndrome, nor with chromosome 5 rings (75,76) or duplications (77,78).…”
Section: Chromosomementioning
confidence: 99%
“…Seizures are not a feature of the well-known "cri du chat" (5p deletion) syndrome, nor with chromosome 5 rings (75,76) or duplications (77,78).…”
Section: Chromosomementioning
confidence: 99%
“…Several investigators described a specific phenotype in a subgroup of patients with autosomal rings independent of which autosome was involved [Côté et al, 1981;Kosztolá nyi, 1987;MacDermot et al, 1990;Freyberger et al, 1991;Migliori et al, 1994]. The major abnormality in those patients is primordial growth failure without malformations and with or without minor anomalies.…”
Section: Introductionmentioning
confidence: 98%
“…Côté et al [1981] proposed the term "ring syndrome" for this group of patients, and more recently Kosztolá nyi reviewed 207 cases with a ring autosome and found that a fifth of the group had the "ring syndrome" phenotype. Most previous reports [McDermott et al, 1977;Zuffardi et al, 1980;Côté et al, 1981;MacDermot et al, 1990;Freyberger et al, 1991;Migliori et al, 1994] have relied on standard cytogenetic banding techniques to exclude deletions in the ring chromosomes. We report on two cases with complete ring (4) and ring (9) chromosomes, respectively, and the "ring syndrome" phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…While some cases of ring chromosomes have been shown to have occurred with no accompanying deletion [MacDermot et al, 1990;Pezzolo et al, 1993;Sigurdardottir et al, 1999;Borovik et al, 2003;Kosho et al, 2005], we have shown, using array-CGH analysis, that small deletions may be present in rings which appear complete by conventional cytogenetic techniques. Referring to the phenotype of our patient, we believe that we have a combination of 2 conditions: the 'ring syndrome' and the partial deletion 2q37.3 phenotype.…”
Section: Discussionmentioning
confidence: 86%
“…The hypothesis of a 'ring syndrome' without deletion was later confirmed by MacDermot et al [1990], Pezzolo et al [1993], Sigurdardottir et al [1999], Borovik et al [2003], and Kosho et al [2005]. MacDermot et al [1990] also were unable to show the loss of genetic material in 3 cases of ring chromosome 5, using G-, R-and Q-banding techniques and scanning electron microscopy.…”
Section: Discussionmentioning
confidence: 90%